Modified infra-promontorium trans-channel approach to the petrous apex. Case report - Khassan M. Diab; Nikolai A. Daikhes; Olga A. Pashinina; Olga S. Panina; Svetlana V. Kokhanyuk; Amina M. Shamkhalova (Consilium Medicum)
This article describes the approach to the petrous pyramid developed at National Medical Research Center of Otorhinolaryngology, namely an endoscopy – microscopy-guided modified trans-channel infra-promontorium approach with internal carotid artery retraction maneuver in patients with lesions of the petrous pyramid but with preserved hearing. A clinical report describing the apical cholesteatoma of the petrous pyramid and the use of this approach are presented. Anatomical and functional features after the surgery are also described. The purpose of this paper is advancing of the surgical approach to the petrous pyramid with the possibility of hearing preservation. The results of surgical treatment in lesions of the petrous pyramid were evaluated in the immediate and distant periods. The functions of facial mimic muscles were evaluated immediately after the surgery, in 6 months, and in one year. The functions of facial mimic muscles remained at the baseline level during the whole follow-up period. The pure tone audiogram demonstrated the preserved hearing function in the postoperative period. Complete elimination of the pathological process was achieved in all cases (n=15); according to the MRI of the temporal bones, no relapses occurred in a year. The surgical approach proposed for patients with the lesions of the petrous pyramid enables complete removal of the pathological process from the petrous pyramid with the preservation of hearing and facial functions, based on the subjective examinations (audiometry, facial function diagnosis) and radiology (CT and MRI of temporal bones) at the preoperative stage.